Pembinaan Pengelolaan Bimbel Smart Education: Strategi E-Coaching Clinic dalam Mengembangkan Teknososiopreneur Mahasiswa PGSD - Munajah, Robiatul; Kilawati, Andi (Universitas Cokroaminoto Palopo, 2024)
This research aims to develop the attitudes and abilities of technosociopreneurs in Semester V PGSD students at Trilogy University through the E-Choaching Clinic strategy. This research is research and development (R&D) using the ADDIE Assessment/Analysis, Design, Development, Implementation and Evaluation model. The subjects of this research were 30 fifth semester students of Trilogy University PGSD. The research instrument used observation sheets and questionnaires. E-coaching clinics are basically guidance designed to improve competencies and attitudes both formally and informally through online media. The e-coaching clinic is a solution to help students develop themselves in carrying out their duties effectively, so that they can develop attitudes and abilities in accordance with the vision and mission of Trilogi Higher Education, which in this case are the attitudes and abilities of technosociopreneurs. The research results show that the development and implementation of e-coaching has succeeded in increasing the knowledge and abilities of technosociopreneurs in managing smart education tutoring for fifth semester PGSD students. The achievement indicators are: initiative aspect achievement 25% (good category), collaboration aspect 12.5% (good category), and independent aspect 30% (good). Then in the aspect of technology utilization it has reached 62.5% and innovation has reached 50% of the expected standards.